Implementation of Collaborative Presentation Model Based on Curriculum in Improving Students' Critical Thinking Abilities in The Pancasila Education in SMPN Tangerang - Elses Diana; Saurav Kumar (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This research aims to improve students' activeness and critical thinking skills through the application of a collaborative presentation model based on the Independent Curriculum in Pancasila Education. The study used the Classroom Action Research (CAR) method, implemented in two cycles, with planning, implementation, observation, and reflection. The subjects were 32 ninth-grade junior high school students. Data collection techniques included observation, interviews, documentation, and assessment of student presentations. The results showed that the implementation of the collaborative presentation model increased student active participation in the learning process. In the first cycle, student engagement reached 68%, increasing to 87% in the second cycle. Students' critical thinking skills also improved, as evidenced by their ability to express opinions, ask questions, and provide feedback during the presentation process. Therefore, the collaborative presentation model based on the Independent Curriculum can be an effective alternative learning strategy for improving the quality of Pancasila Education learning in junior high schools.